Appropriate Use of Limited Interventions vs Extensive Surgery in the Elderly Patient With Spinal Disorders. (October 2015) - Gussous, Yazeed; Than, Khoi; Mummaneni, Praveen; Smith, Justin; Steinmetz, Michael; Ohya, Junichi; Berven, Sigurd
Abstract : Surgical management of spinal deformity is elderly patients is characterized by significant variability. In a value-based health care economy, minimization of risks and maximization of benefit and durability of surgery are a priority. The choice of a surgical approach is a significant determinant of risk, cost, and outcome. Informed choice regarding a surgical approach requires participation of the patient and surgeon. Limited interventions may be appropriate for patients with radicular symptoms and focal pain. More extensive surgery may be required for patients with global imbalance of the spine. The role of minimally invasive approaches in limiting complications and improving outcome remains in evolution. An optimal choice of surgical approach requires consideration of patient preferences, values, comorbidities, and goals of care. ABBREVIATION: MIS, minimally invasive surgery